LEGAL PROTECTION FOR BPJS INPATIENTS DUE TO LIMITED HOSPITAL SPACE - Efrysa Frijon Hutagaol; Andi Maysarah; Dian Hardian Silalahi (NOMOI Law Review, 2026)
Access to healthcare is a constitutional right of citizens guaranteed by law. However, in practice, inpatients participating in the National Health Insurance (BPJS Kesehatan) are still frequently denied referrals by hospitals due to limited inpatient room capacity. This study aims to analyze the legal provisions related to the rights of BPJS Kesehatan patients, examine the legal responsibilities of hospitals and BPJS Kesehatan, and identify forms of legal protection for patients who experience referral denials. This study uses a normative legal method with a statutory and conceptual approach, through a qualitative analysis of secondary legal materials. The results show that denials of inpatient referrals due to limited capacity, without providing alternative referrals, contradict the hospital's obligation to provide healthcare services and its social function as stipulated in the Health Law and related regulations. Legal responsibility for such denials lies with the hospital due to negligence in providing services, and with BPJS Kesehatan due to its weak supervisory function over the referral system. Legal protection for patients includes preventive measures in the form of transparency of bed availability information and integration of hospital information systems, as well as repressive measures in the form of administrative sanctions and civil lawsuits. This study concludes that despite the existence of a regulatory framework, weak law enforcement has resulted in suboptimal protection of patient rights. Therefore, strengthened oversight, real-time integration of hospital management systems, and the implementation of strict sanctions are needed to ensure legal certainty for BPJS Kesehatan participants.